Alvin and the chipmunks [videorecording (DVD)] - Lee, Jason, 1970- (20th Century Fox Home Entertainment, 2008)
Struggling songwriter Dave Seville opens his home to a talented trio of chipmunks named Alvin, Simon, and Theodore. When they become overnight music sensations, a greedy record producer tries to exploit the 'boys.' Now Dave must use a little human ingenuity and a lot of 'munk mischief to get his furry family back before it's too late.